Relocation of hydropower immigrants and transformation of farmers’ energy consumption structure: an empirical study from western China - Zhao, Lei; Du, Xingduan; Zhang, Haixia (Frontiers in Energy Research, 2023)
Based on the research perspective of hydropower migration, the energy consumption structure of farmers in western China was analyzed. The OLS, Probit, and PSM models are used to empirically analyze the impact of the relocation of hydropower immigrants on the household energy consumption structure. The results show that: (1) Although the relocation of hydropower immigrants increases the energy consumption burden of farmers to a certain extent, it has a significant inhibitory effect on the quantity of energy consumption and can promote the improvement of the quality of energy consumption. (2) The age structure of the head of household is different in the impact of the relocation of hydropower immigrants on the energy consumption choices of the households. This difference has different effects on different groups and energy consumption structure, especially in the impact on the energy consumption quality of the households with duality. (3) For low-income households, the economic burden of improving the quality of energy consumption is still large, and income is still an important factor affecting the transformation and upgrading of the energy consumption structure of households. (4) Mechanism analysis shows that the relocation of hydropower immigrants can reduce the dependence of households on the quantity of energy consumption by affecting the increase of non-agricultural income and the decrease of agricultural income, but it cannot affect the quality of households' energy consumption. (5) The moderating effect shows that the relocation of hydropower immigrants can enrich the information types and information elements of farmers, and coordinate the household energy consumption decisions affecting farmers from both digital information and traditional information, thus promoting the transformation and upgrading of the household energy consumption structure of farmers.